2008
DOI: 10.4103/0973-6247.39504
|View full text |Cite
|
Sign up to set email alerts
|

Iron status of regular voluntary blood donors

Abstract: Background:Our blood bank is a regional blood transfusion centre, which accepts blood only from voluntary donors.Aim:The aim is to study iron status of regular voluntary donors who donated their blood at least twice in a year.Materials and Methods:Prior to blood donation, blood samples of 220 male and 30 female voluntary donors were collected. Control included 100 each male and female healthy individuals in the 18- to 60-year age group, who never donated blood and did not have any chronic infection. In the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 4 publications
5
14
1
Order By: Relevance
“…We found no consistent effect of diet on Hb levels, risk of low Hb, or risk of a decrease in Hb of more than 0.5 mmol/L (0.8 g/dL) between donations. The literature is ambiguous on the subject, with an Indian study finding no difference in iron profile between vegetarians and nonvegetarians . Another study found higher hematocrit values and iron levels in vegans and lactoovovegetarians compared with nonvegetarians, while one study from Germany reported iron status to be compromised by a vegetarian diet .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We found no consistent effect of diet on Hb levels, risk of low Hb, or risk of a decrease in Hb of more than 0.5 mmol/L (0.8 g/dL) between donations. The literature is ambiguous on the subject, with an Indian study finding no difference in iron profile between vegetarians and nonvegetarians . Another study found higher hematocrit values and iron levels in vegans and lactoovovegetarians compared with nonvegetarians, while one study from Germany reported iron status to be compromised by a vegetarian diet .…”
Section: Discussionmentioning
confidence: 57%
“…The literature is ambiguous on the subject, with an Indian study finding no difference in iron profile between vegetarians and nonvegetarians. 21 Another study found higher hematocrit values and iron levels in vegans and lactoovovegetarians compared with nonvegetarians, 22 while one study from Germany reported iron status to be compromised by a vegetarian diet. 23 However, given previously published results from the Danish Blood Donor Study, which showed only very limited effect of diet on iron stores, it is not surprising that we did not find any correlation between diet and Hb levels.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to the high number of splenectomized β-TI patients. According to previous studies [21], lower-than-normal levels of serum iron and transferrin saturation were observed in most of the blood donor controls. Nevertheless, in β-TMI blood donors, the levels of these parameters were about twice higher than in controls, even if they were significantly lower than in β-TI patients.…”
Section: Resultsmentioning
confidence: 99%
“…In most countries, strict regulations have been established for the selection of blood donors that incorporate criteria that serve to protect both the donor and recipient,2 but these regulations are not adhered to in most developing countries, including Nigeria. An acceptable frequency of donation is normally two or three times a year or every 12 weeks 3.…”
Section: Introductionmentioning
confidence: 99%